MENERAPKAN PETA KONSEP DALAM MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIKA - Euis Ratna Suminar (JENTRE, 2022)
Concept maps can help students to understand the subject matter because it is not just memorizing, but actually identifying the concepts obtained. In other words, concept maps provide schemas for analyzing new stimuli, and for determining relationships within and between categories. Classroom Action Research is designed for this study. To lead the achieved objectives, the study examines: 1) The process of student learning mathematics after learning using concept maps in each cycle and throughout the cycle, 2) Increasing students' mathematical communication skills in mapping and explaining mathematical concepts by using concept maps, 3) Students' responses to learning mathematics by using concept maps. The results are: 1) An overview of the learning process using concept maps is displayed in form of class photos during learning activities, 2) Mathematical communication skills in each cycle always increases by an average value of the first cycle is 73.15%, the second cycle is 77.15%, and the third cycle is 81.52%, 2) The students' mathematical communication ability after following the entire learning cycle shows good criteria with an average of 83.23%, 3) Based on the attitude scale score analysis, it is obtained that in general, students have a positive attitude towards learning using concept maps.